What does it take to integrate access at live events? A discussion of proactive approaches to access in this diverse setting - Moores, Zoe (The Journal of Specialised Translation, 2023)
Access issues have long been addressed reactively, with subtitling or audio description forming an additional layer to what many consider a final/finished product. As the need for access has become more widely recognised, discussions about access have begun earlier and the very idea that audiovisual products without access might be considered complete is being challenged. Filmmaking and live performance provide examples where access provision is integrated into the production process, yet the question of integrated access at events has not been discussed as fully within media accessibility. In this article, I explore what integrated access at events might look like and consider what a proactive approach involves as we step away from purely media access modalities into the need to embed that access into a more dynamic and participatory setting. After examining what we learn from integrated access in other areas, I focus on peculiarities of the event setting that must be accounted for. I draw on research into respeaking at events which acts as a signpost towards a more integrated approach, and explore guidelines on accessibility and advances in critical event studies to further expand the view. I conclude with a possible framework for supporting proactive access provision.